1979
DOI: 10.1111/j.1365-2125.1979.tb04644.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, pharmacology of atenolol and effect of renal disease.

Abstract: I The pharmacokinetics of intravenous and oral atenolol (50 mg) in six healthy volunteers was studied. Plasma, saliva and urine were collected up to 24 h after each dose.2 There was no significant difference in atenolol half-life when administered by the two routes. Bioavailability of the orally administered atenolol was 50%.3 Atenolol levels in saliva required about 2 h to reach equilibrium with plasma drug levels. 4 A comparison between the pharmacokinetics and pharmacology of atenolol was made in twelve hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
14
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 12 publications
4
14
0
Order By: Relevance
“…The half-life following the 10 mg intravenous dose was considerably shorter than that reported following a 50 mg i.v. dose (Mason et al, 1979;Wan et al, 1979) but very similar to that reported by another group using a 10 mg dose (FitzGerald et al, 1978). The elimination half-life following 50 mg intravenous and oral administration is the same (Mason et al, 1979).…”
Section: Pharmacokinetic Analysissupporting
confidence: 87%
“…The half-life following the 10 mg intravenous dose was considerably shorter than that reported following a 50 mg i.v. dose (Mason et al, 1979;Wan et al, 1979) but very similar to that reported by another group using a 10 mg dose (FitzGerald et al, 1978). The elimination half-life following 50 mg intravenous and oral administration is the same (Mason et al, 1979).…”
Section: Pharmacokinetic Analysissupporting
confidence: 87%
“…Many pharmacokinetic investigations have been carried out for atenolol during the past decades. In humans, the absorption of an oral dose (100-200 mg) of atenolol is rapid and consistent with approximately 50-60% absorbed from the gastrointestinal tract and peak plasma concentrations (1-2 µg/ mL) reached at 2-4 h (Leonetti et al, 1980;Kirch and Gorg, 1982;Wan et al, 1979;Wu et al, 2002Wu et al, , 2003 Sample preparation. Samples were thawed at room temperature and briefly vortex-mixed for 20 s at high speed using a standard multitube vortexer (VWR, West Chester, PA, USA).…”
Section: Introductionmentioning
confidence: 98%
“…Metabolism only plays a negligible role in its elimination, and over 90% of the absorbed atenolol dose can be found as unchanged drug in urine. The mean elimination half-life of atenolol is approximately 6 hr (Wan et al 1979).Also poorly metabolized compounds can be susceptible to pharmacokinetic drug-drug interactions. For instance, plasma concentrations of digoxin and celiprolol can be increased by concomitant itraconazole ingestion (Partanen et al 1996;Lilja et al 2003), and reduced by pretreatment with rifampicin (Greiner et al 1999;Lilja et al 2004).…”
mentioning
confidence: 99%
“…Metabolism only plays a negligible role in its elimination, and over 90% of the absorbed atenolol dose can be found as unchanged drug in urine. The mean elimination half-life of atenolol is approximately 6 hr (Wan et al 1979).…”
mentioning
confidence: 99%